Core temperature and sweating in men and women during a 15-km race in cool conditions - Bongers, C. C. W. G.; ten Haaf, D. S. M.; Ravanelli, N.; Eijsvogels, T. M. H.; Hopman, M. T. E. (International Journal of Sports Physiology and Performance, 2020)
Purpose: Studies often assess the impact of sex on the relation between core body temperature (CBT), whole-body sweat rate (WBSR), and heat production during exercise in laboratory settings, but less is known in free-living conditions. Therefore, the authors compared the relation between CBT, WBSR, and heat production between sexes in a 15-km race under cool conditions. Methods: During 3 editions of the Seven Hills Run (Nijmegen, the Netherlands) with similar ambient conditions (8-12°C, 80-95% relative humidity), CBT and WBSR were measured among 375 participants (52% male) before and immediately after the 15-km race. Heat production was estimated using initial body mass and mean running speed, assuming negligible external work. Results: Men finished the race in 76 (12) minutes and women in 83 (13) minutes (P<.001, effect size [ES]=0.55). Absolute heat production was higher in men than in women (1185 [163] W vs 867 [122] W, respectively, P<.001, ES=1.47), even after normalizing to body mass (15.0 [2.2] W/kg vs 13.8 [1.9] W/kg, P<.001, ES?=?0.56). Finish CBT did not differ between men and women (39.2°C [0.7°C] vs 39.2°C [0.7°C], P=.71, ES=0.04). Men demonstrated a greater increase in CBT (1.5°C [0.8°C] vs 1.3°C [0.7°C], respectively, P=.013, ES=0.31); the sex difference remains after correcting for heat production (P=.004). WBSR was larger in men (18.0 [6.9] g/min) than in women (11.4 [4.7] g/min; P<.001, ES=0.97). A weak correlation between WBSR and heat production was found irrespective of sex (R2=.395, P<.001). Conclusions: WBSR was associated with heat production, irrespective of sex, during a self-paced 15-km running race in cool environmental conditions. Men had a higher CBT than women.